2020
DOI: 10.1155/2020/7284203
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bamboo Plants in Nine Aspects

Abstract: Bamboo forests are undoubtedly one of the most abundant nontimber plants on Earth and cover a wide area of tropical and subtropical regions around the world. This amazing plant has unique rapid growth and can play an important role in protecting our planet from pollution and improving the soil. Bamboo can be used as a biofuel, food, and for architecture and construction applications and plays a large role in the local economy by creating job opportunities. The aim of this paper is to review the extraordinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 97 publications
2
46
0
1
Order By: Relevance
“…Bamboo plants, with 500 species and 70 genera, cover a large part of Chinese forestland (approximately 6 million hectares) [ 25 , 26 ]. Bamboo, with a fast-growing period and high biomass [ 27 ], plays a unique role in the detoxification of the environment and phytoremediation [ 28 ], and bamboo in southern China acts as a forest resource and economically valued plant that is widely involved in the everyday life of local households [ 25 ]. According to the report by the State Forestry Administration of China (2012), the bamboo industry, a growing economy in China, accounts for an excess of $19.7 billion (USD) of China’s local economies [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo plants, with 500 species and 70 genera, cover a large part of Chinese forestland (approximately 6 million hectares) [ 25 , 26 ]. Bamboo, with a fast-growing period and high biomass [ 27 ], plays a unique role in the detoxification of the environment and phytoremediation [ 28 ], and bamboo in southern China acts as a forest resource and economically valued plant that is widely involved in the everyday life of local households [ 25 ]. According to the report by the State Forestry Administration of China (2012), the bamboo industry, a growing economy in China, accounts for an excess of $19.7 billion (USD) of China’s local economies [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes the review by Many excellent reviews on the efficient use and practical applications of bamboo can be found in the bamboo literature, with an emphasis on sustainable bamboo production in the sense of bio-economy and the circular economy [21]. This includes the review by reference [22], explaining the factors that emphasize bamboo growth and strength, as well as identifying ways to utilize bamboo in the industry, employment, climate change mitigation and soil erosion reduction. To date, only a few reports exist on the biotechnological applications for bamboo improvement, particularly related to industrial use.…”
Section: Dendrocalamus Aspermentioning
confidence: 99%
“…Use of natural materials, especially bamboo, in architecture are having a revival in Asia because of its abundance, multifunctionality, and sustainability as locally available materials. (Emamverdian et al 2020;Maslucha et al 2020).…”
Section: Identified Landscape Componentsmentioning
confidence: 99%